2019
DOI: 10.1186/s13287-019-1372-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of exosomes in immune-mediated eye diseases

Abstract: Exosomes, nanosized extracellular vesicles of 30–150 nm, are shed by almost all cell types. Bearing proteins, lipids, RNAs, and DNAs, exosomes have emerged as vital biological mediators in cell-to-cell communication, affecting a plethora of physiological and pathological processes. Particularly, mounting evidence indicates that immunologically active exosomes can regulate both innate and adaptive immune responses. Herein, we review recent advances in the research of exosomes in several immune-mediated eye dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 120 publications
0
55
0
Order By: Relevance
“…Exosomes, the smallest EV fraction (40–200 nm in diameter) ( Théry et al, 2002 ; Vella et al, 2017 ; Hessvik and Llorente, 2018 ; Słomka et al, 2018 ), in particular, have recently been implicated in the pathogenesis of retinal degenerative diseases. These include Age-Related Macular Degeneration (AMD) ( Wang et al, 2009 ; Klingeborn et al, 2017 ; Hsu et al, 2018 ; Li et al, 2019 ), Diabetic Retinopathy ( Huang et al, 2018 ), and Retinitis Pigmentosa ( Vidal-Gil et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes, the smallest EV fraction (40–200 nm in diameter) ( Théry et al, 2002 ; Vella et al, 2017 ; Hessvik and Llorente, 2018 ; Słomka et al, 2018 ), in particular, have recently been implicated in the pathogenesis of retinal degenerative diseases. These include Age-Related Macular Degeneration (AMD) ( Wang et al, 2009 ; Klingeborn et al, 2017 ; Hsu et al, 2018 ; Li et al, 2019 ), Diabetic Retinopathy ( Huang et al, 2018 ), and Retinitis Pigmentosa ( Vidal-Gil et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To conclude, this study demonstrates a simple yet effective peptide modality that is capable of stimulating both cell motility and exosome biogenesis in corneal epithelium, mediated through Lacritin biology. As exosomes mediate cellular communication, signaling, and immune modulation, the biological and therapeutic effects of both exosomes and LP-A96 in the context of dry eye diseases (DED) [ 40 , 41 ] will greatly advance our knowledge towards the pathophysiology of DED and aid in providing a better way to improve daily lives of DED patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that MSC-Exo effects were partly due to the polarization of the lacrimal macrophage as well as the responses of Treg and Th2 by NF-kB signaling pathways. Thus, MSC-Exos may be useful in the treatment of dry eye [113]. Experimental autoimmune uveoretinitis (EAU) could be effectively resolved by the use of bone marrow-derived MSC-Exos [114].…”
Section: Therapeutic Potential Of Exosomes In Autoimmune Diseasementioning
confidence: 99%